Complement activation by cellulosic dialysis membranes. Issue 2 (February 1994) - Innes, A; Farrell, A M; Burden, R P; Morgan, A G; Powell, R J
Abstract : AIMS–To assess the effect of cellulosic dialysis membranes on the production of complement degradation products to determine to the role of the classical pathway. METHOD–Complement activation was studied in 33 patients during a single haemodialysis session using cellulosic membranes. Pre- and post-dialysis plasma EDTA valves of C3, C4, C3dg, C4d and C reactive protein (CRP) were measured. Statistical analysis was done using the Wilcoxon signed rank test. RESULTS–Post-dialysis C4 (p = 0.0003), C3dg (p < 0.0001), and C4d (p = 0.003) concentrations were increased compared with pre-dialysis values. There was no significant change in C3 (p = 0.095) and CRP (p = 0.13) values. Post-dialysis C3dg and C4d concentrations correlated significantly (p = 0.007). IgG, an undialysed molecule, was quantified and post-dialysis valves were significantly higher than those before dialysis (p = 0.0002), indicating a degree of haemoconcentration. To remove this effect, the C3:IgG, C4:IgG, C3dg:IgG, C4d:IgG and CRP:IgG ratios were calculated. Compared with pre-dialysis values, post-dialysis C3dg:IgG and C4d:IgG ratios were increased and C3:IgG decreased significantly. No change was observed in C4:IgG and CRP:IgG ratios. CONCLUSION–This study confirms that significant complement activation takes place following dialysis with cellulosic membranes. This is denoted by an increase in C3dg. This was paralleled by a rise in C4d, implying a contributory role for the classical pathway. Concomitant post-dialysis increases in IgG and C4 indicate a degree of haemoconcentration; but removal of this effect shows that C3dg and C4d are increased following dialysis–suggesting classical, in addition to alternative, pathway activation.